PERCEPTIONS OF AMBITIOUS BEHAVIOR PATTERNS IN STUDENT ACADEMIC COMPETITION - Geofakta Razali; Naurissa Biasini (Mutiara Intelektual Indonesia Press, 2023)
Perception is the process through which we assess others, focusing on the aspects of human behavior we choose to observe. This study delves into the perception of students' ambitious attitudes, an area still shrouded in debate over whether such ambition is beneficial or detrimental within student circles. We conduct a comprehensive analysis of this topic through literature reviews and support it with social judgment theory, which explores the